Peranan - Ruliati, Luh Putu; Limbu, Ribka; Manurung, Imelda; Setyobudi, Agus (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2021)
Pos Upaya Kesehatan Kerja (UKK) is the main activity of Puskesmas which is aimed mainly at informal sector workers in the working area of the Puskesmas, in the context of efforts to prevent and eradicate work diseases and accidents and the work environment. This study aims to determine the role of Pos UKK in improving the health and safety of workers in the informal sector which includes the relationship between knowledge and occupational health, workspace conditions and occupational health, use of PPE with occupational health, fire prevention techniques with occupational health, and health facilities with occupational health. This research used observational method with cross sectional study. The research subjects were 80 informal sector workers who were selected by stratified random sampling. The collected data was analyzed by using correlation test from Spearman with significant level of 95%. The results showed that there was a relationship between knowledge and occupational health, there was no relationship between workspace conditions and occupational health, there was a relationship between the use of PPE and occupational health, there was a relationship between fire prevention techniques and occupational health, and there was a relationship between health facilities and occupational health. The conclusion of this study is the role of Pos UKK that can improve the health and safety of informal sector workers in Kupang City.